WHOSE FAULT? THE SPECULATOR'S GUILT IN LITTLE DORRIT. Issue 2 (5th May 2017) - Lannon, Colleen
Abstract : In May 1855, Charles Dickens confided to a friend that he had found a "capital name" for his new work, Nobody's Fault, a title that remained until he completed the first three numbers and renamed it Little Dorrit ( Letters 7.703). The original title has generally been assumed to refer to Dickens's broad attack on the lack of accountability in government, particularly in relation to the Crimean War. However, the phrase also evokes the issues of financial impropriety that permeate the novel. In particular, Arthur's obsessive concern that through his parents' grasping at money "some one may have been grievously deceived, injured, ruined" (39; bk. 1, ch. 5) links his personal sense of guilt to the more public instance of financial "ruin" in the book – the collapse of Mr. Merdle's fraudulent schemes. In both cases, the question of agency remains ambiguous. Who is at fault for the bankruptcy of Clennam & Doyce: Arthur, who invested the firm's money in Merdle's ventures; Pancks, who convinced him of their soundness; or Merdle, who perpetrated the fraud? And who bears responsibility for the financial deceit that deprived Amy Dorrit of her rightful inheritance from Arthur's grandfather: Mrs. Clennam, who hid the codicil; Arthur's father, who colluded in the concealment; or Arthur, who, along with his parents, benefited financially from the transaction? Out of these ambiguities emerges one figure that becomes the locus of responsibility and blame for both transgressions – Arthur Clennam. Against the express wishes of his solicitor, Arthur steps forward to become the "solitary target" for the "thousands of people. . . wildly staring about for somebody alive to heap reproaches on" in the aftermath of Merdle's downfall and suicide (599; bk. 2, ch. 26). His actions give public expression to his private sense of familial guilt, allowing him to declare openly, " I am at fault."